Norms for eating disorder examination questionnaire (EDE-Q) among secondary school students in Kuala Lumpur, Malaysia. - Musa, Ramli; M.A, Bujang; J, Haniff; NA, Mohamad; K, Omar; Al-Ani, Ali Sabri Radeef (IIUM, 2016)
Introduction: The Eating Disorder Examination Questionnaire (EDE-Q) has been widely used as a tool to detect eating disorders. We aimed to identify the EDE-Q normative data among secondary school students in Kuala Lumpur, Malaysia. Methods: This is a cross-sectional study involving four secondary schools in an urban area. The respondents of secondary school students were selected using stratified sampling. Results: There were 298 teenagers 12 to 17 years of age who participated in the study. The EDE-Q mean scores ± standard deviation was 1.27 ± 1.08 for the total score (Global Score), 0.78 ± 0.95 for Restraint Domain, 1.02 ± 1.03 for Eating Concern, 1.76 ± 1.55 for Shape Concern and 1.54 ± 1.43 for Weight Concern. Conclusion: Mean values obtained from this study were relatively lower when compared to western populations. Shape Concern and Weight Concern had higher scores compared to the other domains. These values are useful for EDE-Q interpretation in Malaysia.